Intervista ad Antoine Volodine (ENTHYMEMA, 2020)
Interview to Antoine Volodine, done in Vercelli (Italy) at the Department of Humanities of the University of Eastern Piedmont on 2nd May 2019.
Keywords: Antoine Volodine; reception; Orient; post-exoticism